Diagnósticos de Enfermagem identificados na alta hospitalar de idosos - SANTOS, Walquiria Lene dos (2008)
The planning of the discharge should begin in the entrance patient in atmosphere hospitalar. This study aims: to identify and analyse the profile of the nursing diagnosis of NANDA (2006), to analyse the following characteristics of the participants: gender, age, education, income and religion, to describe the related factors, risk factors and defining characteristics for diagnoses identified discharge in hospital of elderly, treated in a hospital school of the Region Western-Central. Used a structured form for collect data and the process of clinical reasoning (analysis and synthesis of data) according Risner (1995) for identify the nursing diagnosis. Most elderly people belonged to male sex (72%), age group of 60 to 69 years (52%), married (64%), the profess catholicism (80%), had less than four years schooling (88%) and monthly income of up to one minimum wage (52%), greater than a minimum wage (40%) and without income (8%). The spheres most frequently were: health promotion (100%), protection and security (100%), perception and cognition (96%), self (88%), relationship of paper (88%), coping / tolerance to stress (88%) and activity and rest (84%). The spheres of sexuality (24%) and principles of life (4%) had lower frequency. The diagnosis that received frequency greater than 50% were: damaged teeth (96%), arrangement improved self (80%), arrangement increased confront (80%) arrangement improved processes relatives (76%), infection risk (68%), arrangement increased the control of the therapeutic regimen (64%), sensory perception (visual, olfactory, auditory and tactile) altered (60%), inadequate knowledge about the disease (60%) and arrangement for improved nutrition (52%). The defining characteristics with more frequency were: health care resources are insufficient to impact or prevalence of disease (100%), account the problem (100%), demonstration of disease (100%), locomotion at random (100%), reported experience of forgotten (100%), inability to recall factual information (100%), lack of energy (100%), inability to maintain the level of habitual physical activity (100%), impaired ability to obtain or reinstate articles of apparel (100%), appropriate choices of daily activities to achieve the objectives of a programme of treatment or prevention (90,9%), tiredness (85,7%), acceptance of qualities and limitations (85%) and visual distortions (83.3%). The related factors encountered with more frequency were: sensory perception altered (100%), lack of interest in learning (100%), lack of exposure (100%), lack of familiarity with the use of information (100%), weakness and tiredness (100%), harmful agents (physical) (100%), emotional state especially frustration (100%), state of illness and weakened physical condition (85,7%) and destruction of layers of the skin (80%). The risk factors encountered were: effects of medications (diuretics) (100%), abnormalities of the anal sphincter (100%), invasive procedures (100%), age more than 65 years (100%), respiratory and circulatory problems (83,3%), decreased energy and fatigue (80%) and falls historical (66,6%). The knowledge of nursing diagnosis, by systematization of care realized discharge in hospital of elderly, it should involve the whole family and caregivers, guaranteeing thus, continuity of humanized care, the return of elderly in home